Urgensi Pembaruan Hukum Perlindungan Konsumen dengan Pembentukan Pengadilan Khusus sebagai Upaya Pemenuhan Akses terhadap Keadilan bagi Konsumen - Yuyut Prayuti (UNES Law Review, 2023)
Legal protection for Indonesian citizens, especially consumers, is vital for Indonesia's legal progress. The complexity of consumer protection has grown due to the multitude of products, services, and transaction systems. Globalization has led to increased competition, cross-border investments, international trade, and greater global economic interdependence. Despite consumer rights granted by the GCPL Law, such as the freedom to choose dispute resolution methods, it hasn't ensured easy access or legal certainty. This research proposes a solution, suggesting the creation of a specialized court to address intricate consumer disputes, ensuring access to justice. The research method employed is normative juridical, and it concludes that the GCPL lacks explicit regulations on dispute resolution methods. This is evident through BPSK's inconsistent position, the possibility of objecting to BPSK decisions, and the limitless compensation claims handled by BPSK. Establishing a dedicated consumer court is essential to bolster consumer protection, improve access to legal assistance, and fortify the legal framework for safeguarding consumer rights. Consequently, an amendment to Law No. 8/1999 on consumer protection is needed to establish a Special Consumer Court responsible for deciding consumer disputes through litigation.